Introducing Online Search Services in India : Case Study of an Experimental Project in NAL, Bangalore - Seetharaman, M. N. (Journal of Information and Knowledge, 1987)
Discuss the basic features of an on-line information system for India-After analysing the results of an Experimental system for on line service in India, presents a cost-analysis for installing an international connection to online service in a resource sharing basis.